A service-free wireless sensor solution - Tan, Eugene You Jing (2018)
This project encompasses the designing and development of a service-free wireless sensor system which will incorporate the use of various energy harvesting methods. The progress of the project will lead up to the design of an intruder alert system, which will be evaluated on its potential usage in residential and possibly commercial buildings. The report will discuss the practical options that are available for the development of the system, as well as the considerations that were made for the designing of the hardware and software system, before arriving at the final product. All relevant information pertaining to the designing of the full system can be found within the report, in the respective Chapters and Appendixes.